CONGENITAL HYPOTHYROIDISM WITH DIFFERING PHENOTYPE IN TWO SIBLINGS WITH THE SAME DUOX2 MUTATION - Yusuf, Muhammad Zul Hafiz bin; Zakaria, Noorzeehan; Hwu, Ting Tzer (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Congenital hypothyroidism (CH) is caused by thyroid gland structural or functional defects. Thyroid dysgenesis is typically sporadic but dyshormogenesis is frequently inherited as autosomal recessive. Dual oxidase 2 (DUOX2) gene mutation causes abnormal iodide organification in thyroid hormone synthesis. We report 2 siblings with CH sharing the same mutation in DUOX2, however only one had permanent CH. CASE A 14-year-old female had CH detected at birth by high cord TSH (>100 m IU/L), and thyroid function test (TFT) on day 3 of life (TSH >100 m IU/L, free T4 8.57 pmol/L). Thyroid replacement was started at a dose of 8 mcg/kg/day. Ultrasound at age 3-year-old showed a hypoplastic thyroid gland. She had permanent CH as TFT was deranged when thyroxine was withheld at age 3. Her younger brother, now aged 9 years, had CH diagnosed at age 1 month when he presented with prolonged jaundice (TSH 56.4 m IU/L, free T4 8.89 pmol/L). His cord TSH was normal (7.18 m IU/L). Thyroxine replacement was started at a dose of 7 mcg/kg/ day. Ultrasound at age 3 showed a normal-sized thyroid gland. Thyroxine was stopped at age 3, and subsequent TFT remained normal, indicating transient CH. Both had no goiter, nor comorbidity. No other family members had a thyroid disorder. Parents were non-consanguineous. Whole exome sequencing (3Billion, South Korea) revealed both siblings had the same pathogenic heterozygous DUOX2 mutation (c.3329G>A). It was inconclusive as the second abnormal allele was not detected. CONCLUSION The same DUOX2 mutation can have different phenotypes within the same family. Genetic testing has a role in evaluating CH etiology, especially when at least two family members are affected. Newborn siblings of a child with CH need timely monitoring of TFT if cord TSH is normal. Other genetic methods are needed to detect the second variant of DUOX2 in these siblings.